Saunders nursing drug handbook 2006 - Hodgson ,Barbara B (McGraw-Hill, 2006)
This handbook is a must-have reference for practitioners who seek current, reliable content on medications and comprehensive information on IV drugs. Its alphabetical organization makes it easy to find crucial information quickly. A bound-in CD-ROM includes searchable and printable drug cards, which aid in patient teaching.